EFFECTIVENESS OF THE LANGUAGE OF FAST FOOD ADVERTISEMENTS THROUGH J. BAUDRILLARD'S POSTMODERNISM - Yaghubyan, Marine (Armenian Folia Anglistika, 2022)
One of the dominant fields in the scope of advertising is Fast Food promotion. Junk food advertisements are viral on the Internet, television, billboards and among other types of advertisements. This has led to many people preferring it to other types of food. Several studies have also investigated the effects of junk food advertisements on people’s attitudes and preferences. Firstly, it creates some expectations which raise the desire to buy. Secondly, it associates purchase of these foods with some positive feelings such as satisfaction and happiness. Thirdly, it uses a certain entertaining dimension, thus, implying that purchase will boost a pleasant mood. Finally, people are not always conscious about the persuasive nature of advertising. In this connection, the present article aims to study how some linguistic techniques and devices in Fast Food advertisements call people for certain actions (purchase) and make these advertisements effective. The linguistic analysis of all advertisements carried out in the research mainly focused on defining and characterizing the linguostylistic devices used in fast food advertising, taking into consideration specific language levels such as lexicon, phonology, stylistics and grammar. The analysis demonstrates that nearly every advertisement uses rhetorical figures not depending on the thematic domain they come from.
Keywords: postmodernism; fast food advertisement; language levels; lexicon; phonology; stylistics; grammar